Elastic neutron scattering studies at 96 MeV for transmutation - Michael Österlund (2018)
Elastic neutron scattering from12C,14N,16O,28Si,40Ca,56Fe,89Y and208Pb has been studied at 96 MeV in the10-70° interval, using the SCANDAL (SCAttered Nucleon Detection AssembLy) facility. The results for12C and208Pb have recently been published, while the data on the other nuclei are under analysis. The achieved energy resolution, 3.7 MeV, is about an order of magnitude better than for any previous experiment above 65 MeV incident energy. A novel method for normalisation of the absolute scale of the cross section has been used. The estimated normalisation uncertainty, 3%, is unprecedented for a neutron-induced differential cross section measurement on a nuclear target. Elastic neutron scattering is of utmost importance for a vast number of applications. Besides its fundamental importance as a laboratory for tests of isospin dependence in the nucleon-nucleon, and nucleon-nucleus, interaction, knowledge of the optical potentials derived from elastic scattering come into play in virtually every application where a detailed understanding of nuclear processes is important. Applications for these measurements are dose effects due to fast neutrons, including fast neutron therapy, as well as nuclear waste incineration and single event upsets in electronics. The results at light nuclei of medical relevance (12C,14N and16O) are presented separately. In the present contribution, results on the heavier nuclei are presented, among which several are of relevance to shielding of fast neutrons. © The Author 2007. Published by Oxford University Press. All rights reserved.